BEL462: Reading and Critical Thinking / Academy of Language Studies - UiTM, Academy of Language Studies (2012)
This course is designed to develop students’ ability to read analytically and think critically. It focuses on the relationship between reading and critical thinking and provides students with a structured method for interpreting content of written texts. Tasks and activities suggested are discipline-based.